Percepción visual en la lecto escritura de los estudiantes de la unidad educativa “José María Román” - Ponce Martínez, María Belén (2024)
This study's main objective is to comprehensively evaluate the reading, writing, and perceptual skills of eighth-grade children enrolled in the "José Maria Roman" Educational Unit during their fourth year of primary education. The methodological approach combines quantitative and qualitative components; literacy is assessed with the DR OLEA test, and perceptual skills are examined using the "FROSTIG DTVP-2" visual perception analysis test. A sample of ninety-one students was the research subject, which addressed many factors such as form constancy, location in space, spatial connections, visual closure, and visuomotor speed. Specific tests were used to assess each subarea, comprehensively evaluating the subjects' perceptual ability. Within a mental age range of 5 to 7 years, the findings show remarkable variation in perceptual ability, with a specific gap in shape constancy. Differences in literacy were found, ranging from significant deficits to normal levels. The findings emphasize the need to use early interventions and individualized instructional methodologies to meet each student's requirements accurately. Similarly, suggestions are offered for school curriculum adaptation, the deployment of specialized support programs, and ongoing assessment using specific tools. These steps are considered crucial to providing an inclusive education that adapts to the needs of each student and fosters the full development of cognitive and perceptual abilities.